THE EFFECT OF ISOFLAVONE SOY PROTEIN SUPPLEMENTATION ON ENDOMETRIAL THICKNESS, HYPERPLASIA AND ENDOMETRIAL CANCER RISK IN POSTMENOPAUSAL WOMEN: A RANDOMIZED CONTROLLED TRIAL - Quaas, Alexander M (2013)
OBJECTIVE: To determine whether long-term isoflavone soy protein (ISP) supplementation affects endometrial thickness and rates of endometrial hyperplasia and cancer in postmenopausal women. METHODS: In this randomized, double-blind, placebo-controlled trial, 350 postmenopausal women 45–92 years of age were randomized to a total daily dose of 154 mg of ISP or a milk protein matched placebo for a 3-year period. Women with a surgically absent uterus were excluded from the analysis (final study population: n=224). The main outcome measures were the mean change in endometrial thickness on transvaginal ultrasound from baseline until up to 36 months of follow-up; the incidence of endometrial sampling, endometrial hyperplasia and endometrial cancer. RESULTS: A total of 666 visits among 224 participants were evaluated. Treatment groups did not significantly differ on the mean baseline or on-trial changes in endometrial thickness. Of the 103 placebo-treated participants, 7 (6.8%) underwent an endometrial biopsy; 6 (85.7%) of these biopsies were benign. One woman in the placebo group was diagnosed with complex endometrial hyperplasia with atypia and underwent a hysterectomy. The pathology result from this surgery was Stage IB endometrial cancer. Of the 121 participants in the soy group, 9 (7.4%) underwent an endometrial biopsy. The results were benign in all 9 cases (100%). Although the rate of hyperplasia / malignancy was higher in the placebo group (14.3% versus 0%), the difference was not statistically significant. CONCLUSION: Three-year isoflavone soy protein (ISP) supplementation has no effect on endometrial thickness or rates of endometrial hyperplasia and cancer in postmenopausal women. LEVEL OF EVIDENCE: I